Marigold (Tagetes erecta) extract as potential botanical pesticide against pest of green amaranth (Amaranthus tricolor) vegetable crop - Md Isa, Zul Hasifi (2017)
Green amaranth (Amaranthus tricolor) is consider to be the most popular vegetables in Malaysia but some of it is exposed to the excessive amount of chemical pesticide to improve the quality and yield. The most harmful pest which can reduce the quality of these vegetables is an armyworm (Spodoptera litura). This pest feed on the leaves which later can reduce the quality. The current method used to control this pest is by using chemical pesticide cypermethrin. The introduction of botanical pesticide to these vegetables may reduce the amount of toxicity which is harmful for human consumption and increase the quality and yield of these vegetables. There are many kinds of botanical pesticide that are available to control the insect pest population and some of it may be more effectives than the others. The marigold (Tagetes erecta) extract is one type of known botanical insecticides. The objective is to test the effectiveness of Marigold as botanical pesticide in controlling armyworm and to determine the precise dosage of marigold extract to control army worm in amaranth plants. The project was carried out by setting potted plants of amaranth in polyethylene bags in the field. Each potted plant was assigned randomly a treatment dosage based on five treatments. The first treatment is the control where water was used as the spray. The treatment of marigold paste extract were 50g,150g, and 200g were dissolved in 500mL of water and was used to spray on green amaranth. Treatments will be applied weekly. Plant growth and development of amaranth will be monitored weekly. The expected result would probably the potential use of marigold paste extract as botanical pesticide in controlling pest on green amaranth. Comparison of results among treatment dosage might give the right dosage of marigold paste extract as botanical pesticide.